Personification in cecimpedan: the semantic structure of the tradition of balinese children - Arnawa, Nengah (Opción, 2019)
This research aims to provide linguistic analysis of the Balinese language characteristics in cecimpedan. The analysis is based on the theory of semantic structure. The research data was collected from audio-visual recordings, a book of Balinese proverbs, traditional art performances scene, children’s pop songs, and informants. Based on the analysis, the characteristics of the Balinese language in cecimpedan are as follows. As a result, the reasoning of inductive and declarative analogy is the mental activity that dominates the participants in macecimpedan activity. In conclusion, the use of personification is a grammatical demand centered on verbs.